277 Temporal trends of advanced 2D-speckle tracking echocardiography in trastuzumab treated patients. (8th December 2021) - Springhetti, Paolo; Bergamini, Corinna; Niro, Lorenzo; Ferri, Luisa; Benfari, Giovanni; Cerrito, Luca Felice; Schiavone, Arianna; Setti, Elisa; Dal Porto, Marta; Tadiello, Enrico; Luisi, Ilaria; Rossi, Andrea; et al.
Abstract: Aims: Trastuzumab (TZ) is widely used for his key role in HER2 positive breast cancer. However, it may have different side effects on the cardiovascular system. One of the most concerning complication is cardiotoxicity. Many studies have highlighted the importance of the screening for subclinical myocardial dysfunction using left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS). However, there are few studies investigating the left atrial function in relation to the development of early cardiac damage. Aim of this study is to analyse the modification of GLS and PALS in patients undergoing therapy with TZ in a follow-up period of 12 months. The eventual fluctuation of left atrial function under chemotherapy was evaluated and the correlation between subclinical atrial disfunction and early left ventricular impairment was searched. Methods: One hundred and five women affected by non-metastatic HER-2 positive breast cancer treated with TZ were enrolled. Each patient underwent a complete echocardiography every 3 months, for a total of five exams pro patient. Thirty-seven patients (35%) were excluded from the left atrial function analysis while LV function evaluation was performed in 83 patients (21%). Exclusion criteria were poor quality imaging and lack of a complete Follow-up with consequent missing data. 2D-Speckle tracking analysis was performed at baseline and at each examination using Tomtec software in order to analyse both atrial and left ventricular function. Subclinical LV disfunction was defined as a GLS reduction of ≥ 15% compared to the baseline value. Left atrial impairment was arbitrary defined as a PALS reduction of ≥ 25% compared to the initial value. Finally, trends of GLS and PALS during 12 months-Follow-up periods were analysed. Results: A total of 48.9% patients developed subclinical LV dysfunction. Similarly, 48.3% patients showed a left atrial impairment. Interestingly a significant ( P  = 0.0001) reduction in GLS was observed during the follow-up, particularly in the first 6 months of treatment. PALS showed a similar trend with a significant decrease during the whole 12 months-follow-up ( P  = 0.0001) and mostly in the first 6 months. Only 11% patients showed a significant reduction of LVEF defined as an absolute reduction of LVEF >10% from baseline. Conclusions: In HER 2 positive breast cancer patients treated with Trastuzumab development of left atrial impairment in not uncommon and PALS modifications follow a similar pattern to GLS variations during the treatment course, suggesting a possible cardiotoxic effect of such therapy on both atrial and left ventricular myocardium and physiology. However, the potential role of an early atrial impairment detection in predicting subsequent cardiotoxicity in terms of significant LVEF reduction still needs to be tested with further studies.